2016
DOI: 10.1037/a0039496
|View full text |Cite
|
Sign up to set email alerts
|

Problem-focused coping mediates the impact of intimate partner violence on mental health among Chinese women.

Abstract: Objective: Our study focused on understanding on the ways that abused Chinese women cope and aimed to examine the mediating role of coping strategies between the relationships of intimate partner violence (IPV; including partner stalking) and mental health problems. Method: A population-based household survey was completed by 550 Chinese community-dwelling women. Data on the mediating roles of coping strategies were examined using structural equation models. Results: The prevalence of IPV among Chinese women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
4
17
0
Order By: Relevance
“…Studies conducted in different countries have reported increased risks for mental health symptoms, such as depression, posttraumatic stress disorders (PTSD), and suicidality (Ferrari et al, 2014;Gibbs et al, 2018;McLaughlin et al, 2012;Nathanson et al, 2012); different health concerns (Alhalal, 2018;Al-Modallal, 2016;Eaton et al, 2016;Massetti et al, 2017); and financial hardships and housing insecurity (Adams et al, 2013;Gilroy et al, 2016). Women face challenges and barriers when seeking help for IPV even though timely and sufficient support for IPV can significantly mitigate these risks (Grip et al, 2011;Guay et al, 2019;Rizo et al, 2017;Wong et al, 2016;. Helpseeking for IPV is an ongoing and dynamic process (Kennedy et al, 2012;Liang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in different countries have reported increased risks for mental health symptoms, such as depression, posttraumatic stress disorders (PTSD), and suicidality (Ferrari et al, 2014;Gibbs et al, 2018;McLaughlin et al, 2012;Nathanson et al, 2012); different health concerns (Alhalal, 2018;Al-Modallal, 2016;Eaton et al, 2016;Massetti et al, 2017); and financial hardships and housing insecurity (Adams et al, 2013;Gilroy et al, 2016). Women face challenges and barriers when seeking help for IPV even though timely and sufficient support for IPV can significantly mitigate these risks (Grip et al, 2011;Guay et al, 2019;Rizo et al, 2017;Wong et al, 2016;. Helpseeking for IPV is an ongoing and dynamic process (Kennedy et al, 2012;Liang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Information on prevalence was usually reported as part of the results in studies that screened for IPV during the recruitment procedure. In this scoping review, the lifetime prevalence of IPV among women was 43%, and the past-year prevalence ranged from 11·5% to 26%; [61 , 68] more specifically, the past-year prevalence of psychological abuse was reported as 22·9%, followed by physical abuse ranging from 6·5% to 10·1%, and sexual abuse ranging from 2·2% to 4·0% [69 , 70] . Prevalence ranged according to setting and sampling procedures; most were convenience samples.…”
Section: Resultsmentioning
confidence: 90%
“…Whereas the conceptualization of suicide within society implies incompetence and incapacitation, Hunting is a novel way of understanding suicide as it depicts women as active agents in determining their health outcomes. Studies demonstrating women’s capacity to protect themselves from the negative mental health effects of violence (Wong et al, 2016; Wuest et al, 2003) substantiate the agency implicit in the Hunting process.…”
Section: Resultsmentioning
confidence: 99%